Home page for accesible maths 6 Linear transformations

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.2. Linear transformations versus matrices

The purpose of this section is to emphasize the following correspondence:

Linear transformations T Composition of functions, TS T(xy)  
Matrices
A
Matrix multiplication, A B
( a 11 a 12 a 21 a 22 ) ( x y )

For every linear transformation we will assign exactly one matrix to it (Definition 6.2.5), and for every matrix there is exactly one linear transformation which it defines (Example 6.1). This type of correspondence is called a bijection or a bijective correspondence, and above this is indicated by the two-way array .

An advantage of writing transformations using matrices is that it makes some computations easier; for example, composition of maps is given by matrix multiplication. If TA,TB are transformations with matrices A,B respectively, then the composition TATB is equal to TAB. This is, in fact, the reason why matrix multiplication is defined the way it is.

Recall that composition of maps reads right to left, i.e. TATB means ‘first do TB, then TA’. This matters because in general TBTATATB. For convenience, we often write TATB instead of TATB.

Example 6.2.1.

  • Consider the following matrices:

    A:=(1201),B:=(03-10).

    Then their associated linear transformations can be written as

    TA(x,y)=(x+2y,y),TB(x,y)=(3y,-x).

    Let’s calculate the composition:

    (TATB)(x,y)=TA(3y,-x)=(3y-2x,-x).

    This is the linear transformation associated to the matrix AB=(-23-10), as expected.

Throughout this section, we consider the Euclidean plane 2, and transformations 22. But you should know that linear transformations nm correspond to m×n matrices in exactly the same way. We will look at the M2() case because it is easiest to visualise.

The standard basis vectors of 2 are {e1,e2} (See Definition 1.4.8). So we have already two equivalent ways of writing the same vector, given by the left and right hand sides of the following equation:

(ab)=ae1+be2.

We will use the following notation for points in 2:

(a,b)2.

Notice this notation is different from the 1×2 matrix (ab) because of the comma.

Remark 6.2.2.

Points and vectors in n can be identified with each other. Explicitly, a point P=(x,y) corresponds to the vector from O to P, OP=(xy), where O=(0,0) (see Figure 4). Thus, the convention is that we write the coordinates of points horizontally with commas between them, and the vectors vertically, as column vectors. In practice, it is usually okay to equate the two in your head. We use the notation to emphasize the different perspectives of “vectors” versus “points”, and it is common to switch between the two.

Figure 4. The vector and point corresponding to the pair (a,b)2
Proposition 6.2.3.

Let T1,T2:R2R2 be linear transformations. Then the composition T2T1 is also a linear transformation.

Proof.

Let λ and pick any vectors v,w2. We have

T2T1(v+w) =T2(T1(v+w))=T2(T1(v)+T1(w)) since T1 is linear
=T2(T1(v))+T2(T1(w)) since T2 is linear
=T2T1(v)+T2T1(w)
and
T2T1(λv) =T2(T1(λv))=T2(λT1(v)) since T1 is linear
=λT2(T1(v)) since T2 is linear
=λT2T1(v)

which proves that LT1 and LT2 hold. ∎

Theorem 6.2.4.

Any linear transformation of R2 is determined by its effect on the standard basis vectors e1 and e2. In other words, a linear transformation T is entirely known if T(e1) and T(e2) are given.

Proof.

Since any vector can be written in the form ae1+be2, where a,b, by linearity we have T(ae1+be2)=aT(e1)+bT(e2). ∎

Definition 6.2.5.

Given a linear transformation T of 2, and let a11,a12,a21,a22 be defined as

T(e1)=a11e1+a21e2andT(e2)=a12e1+a22e2.

The matrix A=(a11a12a21a22) is called the matrix associated to the linear transformation T.

Remark 6.2.6.
  • There is nothing special about the 2 case here; this definition could be generalised to higher dimensions.

  • In fact, A is the matrix of T with respect to the standard basis {e1,e2} of R2. In more general situations, such as in MATH220, one could use a different basis, which would produce a different matrix.

  • We will also say that T is the linear transformation given by the matrix A.

Theorem 6.2.7.

Let A, B be the matrices of the linear transformations T and S of R2. Then

  1. (i)

    T(xy)=(a11a12a21a22)(xy)=A(xy).

  2. (ii)

    AB (matrix multiplication) is the matrix of the linear transformation TS.

Proof.

We have that (xy)=xe1+ye2. Thus

T(xe1+ye2) =xT(e1)+yT(e2) by linearity
=x(a11e1+a21e2)+y(a12e1+a22e2) by Definition 6.2.5
=(xa11+ya12)e1+(xa21+ya22)e2
=(a11x+a12ya21x+a22y)=(a11a12a21a22)(xy) by Definition 1.3.1.

This proves part (i).

For part (ii), let C be the matrix of TS, which is a linear transformation by Proposition 6.2.3. So

T(S(e1))=(TS)(e1)=c11e1+c21e2.

On the other hand, we have that

T(S(e1)) =T(b11e1+b21e2) since B is the matrix for S
=b11T(e1)+b21T(e2) by linearity of T
=b11(a11e1+a21e2)+b21(a12e1+a22e2)
=(a11b11+a12b21)e1+(a21b11+a22b21)e2.

Equating coefficients of e1, we find that c11=a11b11+a12b21, while equating coefficients of e2, we get c21=a21b11+a22b21. A similar calculation for T(S(e2)) gives expressions for c12 and c22 in terms of a11,,a22 and b11,,b22, and in all four cases we see that cij is equal to the (i,j) coefficient of the matrix product AB defined in Definition 1.4.1; that is, C=AB. ∎

Proposition 6.2.8 (Rotation transformations).

In coordinates, anticlockwise rotation through the angle θ is given by

Rθ(x,y)=(xcosθ-ysinθ,xsinθ+ycosθ)for all (x,y)2.

So a rotation around the origin is represented by the matrix

Rθ=(cosθ-sinθsinθcosθ).

In particular, it is a linear transformation.

Proof.

Assume the vector v=(xy) makes an angle α above the positive x-axis. The length of v is r=x2+y2 (see Definition 1.3.5), so we can use polar coordinates to write P=(x,y)=(rcosα,rsinα). When P is written in polar coordinates, it makes an angle α+θ with the x-axis, so we have P=(x,y)=(rcos(α+θ),rsin(α+θ)). Now we can use trigonometric identities as follows:

x =rcos(α+θ)=r(cosθcosα-sinθsinα)
=(rcosα)cosθ-(rsinα)sinθ
=xcosθ-ysinθ
and
y =rsin(α+θ)=r(sinθcosα+cosθsinα)
=(rcosα)sinθ+(rsinα)cosθ
=xsinθ+ycosθ.

This proves the results. ∎

Proposition 6.2.9 (Reflection transformations).

In coordinates, the reflection about the line lθ, whose angle above the x-axis is θ, is given by

Hθ(x,y)=(xcos2θ+ysin2θ,xsin2θ-ycos2θ)for all (x,y)2.

So it may be represented by the matrix

Hθ=(cos2θsin2θsin2θ-cos2θ).

In particular, it is a linear transformation.

Proof.

Let P=(x,y) be the image of P=(x,y)2, as in Figure 3. If the vector corresponding to P makes an angle α above the x-axis, then the angle between l and v is θ-α. Therefore, P is obtained from P by a rotation through 2(θ-α). So the angle P makes with the x-axis is 2(θ-α)+α=2θ-α. Therefore, using trigonometric identities and polar coordinates (see the rotational case above),

x =rcos(2θ-α)=r(cos2θcosα+sin2θsinα)
=xcos2θ+ysin2θ
and
y =rsin(2θ-α)=r(sin2θcosα-cos2θsinα)
=xsin2θ-ycos2θ.

Now we have seen the examples of the rotation around the origin, and of a reflection about a line. We found that for any angle θ[0,2π), they are represented by the matrices

Rθ=(cosθ-sinθsinθcosθ)andHθ=(cos2θsin2θsin2θ-cos2θ).

We showed this by using trigonometric identities. But there is a faster geometric way: consider the Figures 2 and 3, and see where e1 and e2 are mapped:

Rθ(e1)=(cosθsinθ), Rθ(e2)=(-sinθcosθ)
Hθ(e1)=(cos2θsin2θ), Hθ(e2)=(sin2θ-cos2θ).

So the matrices we found in Propositions 6.2.8 and 6.2.9 are correct.

Example 6.2.10.

  • Prove that we have the equality Rπ/3H0=Hπ/6.

  • Solution: The LHS is the composition of the reflection about the x-axis followed by the anticlockwise rotation through π3, while the RHS is the reflection about the line which makes an angle π6 with the x-axis. To prove the claim, let us calculate with their associated matrices:

    Rπ/3H0=(12-323212)(100-1)=(123232-12)=(cosπ3sinπ3sinπ3-cosπ3)=Hπ/6.

    Their associated matrices are equal, and therefore these linear transformations are equal.